ethnographic and geopolitical factors Arab regional system (Journal of the College of Basic Education, 2023)
The state as a political region is sovereign over its land and people, but its division into sectsethnicity that may threaten the political entity of the state and may destroy it from the inside, dividing it or working on the separationA part or parts of it is reflected in the geopolitical weight of that country.The research problem is that the variation in the geographical distribution of the ethnographic components(ethnic structure) indicates in the Arab regional system and the research hypothesis: that the ethnic structureThe community marks the outskirts and heart of the Arab regional system.The importance of research and the need for it stems from its study of the ethnographic components and their impact on the system.Arab regional, because it is of importance because of its impact on the political weight of the regime because of theDangerous, sometimes leading to the dangers of division and the disintegration of the political unity of the state.